1999
DOI: 10.1046/j.1365-3040.1999.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated ozone on CO2 uptake and leaf structure in sugar maple under two light environments

Abstract: The interactive effects of ozone and light on leaf structure, carbon dioxide uptake and short-term carbon allocation of sugar maple (Acer saccharum Marsh.) seedlings were examined using gas exchange measurements and 14 Cmacroautoradiographic techniques. Two-year-old sugar maple seedlings were fumigated from budbreak for 5 months with ambient or 3 × ambient ozone in open-top chambers, receiving either 35% (high light) or 15% (low light) of full sunlight. Ozone accelerated leaf senescence, and reduced net photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 44 publications
9
35
1
Order By: Relevance
“…We conclude that the assimilation rates of the seedlings were not limited by light availability, resulting in a similar total carbon gain and a similar growth rate for seedlings in both light treatments. Leaf morphology, structure and thickness are known to differ with increasing irradiance levels [2,51]. However, in our study, specific leaf mass values were similar at both irradiance levels.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…We conclude that the assimilation rates of the seedlings were not limited by light availability, resulting in a similar total carbon gain and a similar growth rate for seedlings in both light treatments. Leaf morphology, structure and thickness are known to differ with increasing irradiance levels [2,51]. However, in our study, specific leaf mass values were similar at both irradiance levels.…”
Section: Discussioncontrasting
confidence: 57%
“…O 3 is formed by the photochemical reaction between anthropogenic and biogenic nitrogen oxides (NOx), and volatile organic compounds (VOCs) in polluted air masses. In contrast to other gaseous anthropogenic pollutants such as SO 2 , tropospheric O 3 concentration is increasing, probably due to the increase in the levels of NO x and VOC emissions [21]. Increase in global tropospheric O 3 concentration during the 21st century was projected by a range of global emission scenarios studied by the IPCC 2001 assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was supposed that remobilization of resource from senescing leaves to younger ones could allow the latter to withstand ozone stress [21], but this hypothesis needs more experiments to test. The increase of intercellular space during leaf development possibly enhanced the susceptibility to ozone by increasing the ozone dose into per cell, as suggested for leaves of sugar maple seedlings [22]. However, Bagard et al demonstrated that the expanding leaves of hybrid poplar showed higher resistance to O 3 with the same uptake of O 3 as the fully expanded leaves, and proposed that further work was needed to ascertain whether the contribution of the antioxidant capability was responsible for the higher resistance of young leaves [18].…”
Section: A Effects Of Elevated O 3 On Malondialdehyde and Hydrogen Pmentioning
confidence: 74%
“…Ozone may interfere with control of the stomatal aperture and may have the potential to disturb the water balance of the leaf, or even the whole plant (Pearson and Mansfield 1993). Elevated O 3 levels have been shown to influence leaf differentiation during its formation (Frey et al 1996;Bäck et al 1999). Leaf differentiation changed towards xeromorphism, somewhat resembling sun leaves or leaf development under mild drought conditions (Matyssek et al 1991).…”
Section: Introductionmentioning
confidence: 99%